2009 International Conference on Sustainable Power Generation and Supply 2009
DOI: 10.1109/supergen.2009.5348322
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of IEC 61850 process bus architecture on numerical protection systems

Abstract: The deployment of IEC 61850 process bus in substations calls for an impact evaluation of possible process bus architecture scenarios on the performance of numerical protection systems. Six alternative system architectures are proposed based on a component redundancy perspective. The functionality of each system is assessed using reliability block diagrams based on a success-oriented network. System reliability is calculated using the minimal tie sets method determined by the connection matrix. Sensitivity anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…To observe the effects of fault tolerance on network reliability, the sensor nodes are modeled with a seriesparallel RBD configuration in this case. Similarly RBDs have been used to assess the reliability of many other fault tolerant communication networks including wireless sensor networks (WSNs) [84], multistage interconnection networks (MINs) [85], wide area networks (WANs) [86], numerical protection systems [87] and electric power communication networks [88].…”
Section: Analytical Methods With Rbdmentioning
confidence: 99%
See 1 more Smart Citation
“…To observe the effects of fault tolerance on network reliability, the sensor nodes are modeled with a seriesparallel RBD configuration in this case. Similarly RBDs have been used to assess the reliability of many other fault tolerant communication networks including wireless sensor networks (WSNs) [84], multistage interconnection networks (MINs) [85], wide area networks (WANs) [86], numerical protection systems [87] and electric power communication networks [88].…”
Section: Analytical Methods With Rbdmentioning
confidence: 99%
“…A summary of the literature on reliability assessment of communication networks using RBD-based modeling with analysis performed through analytical and simulation methods for RBD models is presented in Table 3 whereas the literature involving reliability analysis using formal methods is summarized in Table 4. [83] A fault tolerant WSN system is modeled using the series-parallel configuration of RBD [84] A framework is presented to incorporate the data transmission problem and is modeled using the series configuration of RBD [85] The pars network, i.e., a fault tolerant interconnection network, is presented and its reliability analysis is performed using RBD [86] The reliability analysis of different protection systems, for the PON architecture, is performed using RBD technique [87] The reliability analysis of smart grid substation is performed using the RBD technique while considering the dynamic behavior of the systems [88] The reliability analysis of different bus architectures, which are deployed in substation communication system, is performed using the RBD technique Data Transmission System [94] The data transmission process of the WSN is presented and modeled using parallel-series configuration of RBD [95] The reliability of SEN is analyzed using RBD and the impact of switching stages on reliability is observed [106] The RBD-based reliability and availability of smart grid substation automation system is analyzed by considering various Ethernet switch architectures…”
Section: Formal Methods With Rbdmentioning
confidence: 99%
“…Several network topologies in digital substations are presented in [2][3][4], and applies RBD(reliability block diagram) method to compare their reliability based on component failure modes. In [5] GO (goal oriented) measure is utilized to calculate the availability and cost of protection system.…”
Section: Reliability Of Substation Lanmentioning
confidence: 99%
“…However, there are numerous communication architectures available each has its own advantages and disadvantages. It is important to select the right architecture for a specific application [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A significant work is reported in the literature to evaluate the reliability and ETE delay performance of time-critical messages in IEC 61850 substations. [11][12][13] T. Skeie et al 14 demonstrated the feasibility of designing switched-Ethernet based SCN that fulfills the real-time demands of protection functions. T. S. Sidhu et al 15 introduced the designing of IEC 61850 IED models in OPNET and then analyzed the dynamic performance of SCNs in traditional Ethernet network topologies.…”
Section: Introductionmentioning
confidence: 99%